Endoprótesis fenestrada para el tratamiento del aneurisma de la aorta abdominal: primer caso en la Argentina - Rostagno, Roman; Cesáreo, Vicente; Peralta, Oscar; Domenech, Alberto; Bracco, Daniel; García Mónaco, Ricardo (Revista del Hospital Italiano de Buenos Aires, 2007)
-